Promising source material for winter triticale breeding under the conditions of the Middle Urals - G. N. Potapova; N. L. Zobnina; A. V. Bezgodov; M. S. Ivanova (Труды по прикладной ботанике, генетике и селекции)
Background. The northern border of cereal crop cultivation passes through the territory of Sverdlovsk Province. Cultivars of winter triticale developed in the regions of Russia located to the south are grown there, but they die under unfavorable winter conditions. The breeding of this crop in local climate is at an early stage, so a study of source material for breeding new highyielding cultivars adapted to local conditions seems quite pertinent.Materials and methods. In 2017–2020, the Ural Research Institute of Agriculture in Yekaterinburg conducted a study of 78 winter triticale genotypes from 10 regions of Russia and 7 foreign countries. The seeds were obtained from the VIR genebank and breeding centers of Russia. Sowing was carried out in clean fallow on August 20–25 on 1 m2 plots in 3-4 repetitions, with the reference ‘Bashkirskaya korotkostebelnaya’ sown on every 10th plot. Plants were assessed for winter hardiness, yield, density of productive stems, plant height, ear length, number of spikelets and grains per ear, weight of 1000 grains, and ear productivity in accordance with published guidelines.Results. Cvs. ‘Privada’, ‘Tsekad 90’ and ‘Nemchinovsky 58’ combined high winter hardiness (70–81%) with resistance to damage by snow mold (15–20%), high density of productive stems (324–425 pcs/m2), and high yield (562–616 g/m2). They had high 1000 grain weight (45.4–49.1 g) and ear productivity (2.63–2.68 g). High yield (571–670 g/m2) and density of productive stems (285–436 pcs/m2 ) with reduced winter hardiness (62–72%) and resistance to snow mold (30–35%) was observed in cvs. ‘Sirs 57’, ‘Sotnik’, ‘Germes’, ‘Antey’, ‘Beta’, ‘Don’, and lines 1/1 and 8003 from Sweden.